The Queerness of Childhood Essays from the Other Side of the Looking Glass - Fishzon, Anna.; Lieber, Emma. (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2022)
This book represents a meeting of queer theorists and psychoanalysts around the figure of the child. Its intention is not only to interrogate the discursive work performed on, and by, the child in these fields, but also to provide a stage for examining how psychoanalysis and queer theory themselves interact, with the understanding that the meeting of these discourses is most generative around the queer time and sexualities of childhood. From the theoretical perspectives of queer theory, psychoanalysis, anthropology, and gender studies, the chapters explore cultural, aesthetic, and historical forms and phenomena that are aimed at, or are about, children, and that give expression to and make room for the queerness of childhood. Anna Fishzon is a psychoanalyst in private practice and an interdisciplinary scholar in New York City. She has taught courses on Russian history, psychoanalysis, literature, and gender and sexuality at Williams College, Columbia University, and Duke University, USA. She is the author of Fandom, Authenticity, and Opera: Mad Acts and Letter Scenes in Fin-de-Siècle Russia (Palgrave, 2013). Emma Lieber is a psychoanalyst in private practice and part-time faculty in Literary Studies at Eugene Lang College, USA, where she teaches courses on psychoanalysis and literature, autotheory, and feminist literature. She is the author of The Writing Cure (2020) and has written articles and essays for numerous academic, popular, and psychoanalytic publications.
1. Introduction: The Queer Child and the Childish Queer -- 2. Parenting the Atemporal Child -- 3. Progressive Penology Meets Youthful Queerness in the Interwar United States -- 4. First Love -- 5. Home You Carry With You -- 6. Our Babies, Ourselves: From Little Spirits to Wired for Love -- 7. The Cultivation of Queer and Trans Childhood: Eugenic Logics of Genetics and Endocrine Sciences -- 8. On Growing Up: A Cautionary Tale for Psychoanalysts -- 9. Adults Only: Lee Edelman's No Future and the Limits of Queer Critique -- 10. Philosophy for Children and the Wonder Kids -- 11. Enigmatic Signifiers and Sexuality Afterwards -- 12. Queue Time, Animation, and the Queer Childhood of Late Socialism -- 13. The Deer Inbetween -- 14. Afterword.
Keywords: Popular Culture; Youth-Social life and customs; Sex; Queer theory; Popular Culture; Youth Culture; Gender Studies; Queer Studies